TaxTajweez: A Large Language Model-based Chatbot for Income Tax Information In Pakistan Using Retrieval Augmented Generation (RAG) - Mohammad Affan Habib; Shehryar Amin; Muhammad Oqba; Sameer Jaipal; Muhammad Junaid Khan; Abdul Samad (Proceedings of the International Florida Artificial Intelligence Research Society Conference)
The advent of Large Language Models (LLMs) has heralded a transformative era in natural language processing across diverse fields, igniting considerable interest in domain-specific applications. However, while proprietary models have made significant strides in sectors such as medicine, education, and law through tailored data accumulations, similar advancements have yet to emerge in the Pakistani taxation domain, hindering its digital transformation.